New insights into Trypanosoma cruzi evolution, genotyping and molecular diagnostics from satellite DNA sequence analysis. - Juan C Ramírez; Carolina Torres; María de Los A Curto; Alejandro G Schijman (Public Library of Science (PLoS), 2017)
Trypanosoma cruzi has been subdivided into seven Discrete Typing Units (DTUs), TcI-TcVI and Tcbat. Two major evolutionary models have been proposed to explain the origin of hybrid lineages, but while it is widely accepted that TcV and TcVI are the result of genetic exchange between TcII and TcIII strains, the origin of TcIII and TcIV is still a matter of debate. T. cruzi satellite DNA (SatDNA), comprised of 195 bp units organized in tandem repeats, from both TcV and TcVI stocks were found to have SatDNA copies type TcI and TcII; whereas contradictory results were observed for TcIII stocks and no TcIV sequence has been analyzed yet. Herein, we have gone deeper into this matter analyzing 335 distinct SatDNA sequences from 19 T. cruzi stocks representative of DTUs TcI-TcVI for phylogenetic inference. Bayesian phylogenetic tree showed that all sequences were grouped in three major clusters, which corresponded to sequences from DTUs TcI/III, TcII and TcIV; whereas TcV and TcVI stocks had two sets of sequences distributed into TcI/III and TcII clusters. As expected, the lowest genetic distances were found between TcI and TcIII, and between TcV and TcVI sequences; whereas the highest ones were observed between TcII and TcI/III, and among TcIV sequences and those from the remaining DTUs. In addition, signature patterns associated to specific T. cruzi lineages were identified and new primers that improved SatDNA-based qPCR sensitivity were designed. Our findings support the theory that TcIII is not the result of a hybridization event between TcI and TcII, and that TcIV had an independent origin from the other DTUs, contributing to clarifying the evolutionary history of T. cruzi lineages. Moreover, this work opens the possibility of typing samples from Chagas disease patients with low parasitic loads and improving molecular diagnostic methods of T. cruzi infection based on SatDNA sequence amplification.